2020
DOI: 10.1038/s41598-020-66197-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation markers panel can improve prediction of response to neoadjuvant chemotherapy in luminal B breast cancer

Abstract: Despite the advantages of neoadjuvant chemotherapy (nAct), associated toxicity is a serious complication that renders monitoring of the patients' response to nAct highly important. thus, prediction of tumor response to treatment is imperative to avoid exposure of potential non-responders to deleterious complications. We have performed genome-wide analysis of DnA methylation by XmaI-RRBS and selected CpG dinucleotides differential methylation of which discriminates luminal B breast cancer samples with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…DNA methylation is the most studied epigenetic mechanism that is highly involved in the regulation of gene expression in BrCa cells [3]. Aberrant methylation in BrCa tissues or in liquid biopsies has been characterized and correlated to diagnosis [4][5][6], prognosis [7][8][9] and the prediction of treatment response [10,11], leading to emerging biomarkers in the BrCa management cascade. Recently, the introduction of genome-wide methylation analyses enables the simultaneous study of up to hundreds of thousands of CpG sites, and produces highdimensional datasets which can allow in-depth understanding of the events of methylation in BrCa pathogenesis, as well as its translation to clinical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is the most studied epigenetic mechanism that is highly involved in the regulation of gene expression in BrCa cells [3]. Aberrant methylation in BrCa tissues or in liquid biopsies has been characterized and correlated to diagnosis [4][5][6], prognosis [7][8][9] and the prediction of treatment response [10,11], leading to emerging biomarkers in the BrCa management cascade. Recently, the introduction of genome-wide methylation analyses enables the simultaneous study of up to hundreds of thousands of CpG sites, and produces highdimensional datasets which can allow in-depth understanding of the events of methylation in BrCa pathogenesis, as well as its translation to clinical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Published literature on promoter methylation of ADCY8, CDH8 , and ZNF582 has expanded recently and hypermethylation of one or more of these loci have been found in cancers of the breast, oropharynx, esophagus, and anus ( Tang et al, 2019 ; Ekanayake Weeramange et al, 2020 ; Sigin et al, 2020 ; van der Zee et al, 2020 ). These reports not only support the validity of these epigenetic modifications as cancer biomarkers but inform a broader application beyond cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First, differential methylation of ADCY8 was identified as one of three most informative biomarkers in luminal B breast cancer from a cohort of Russian women. Methylation status of these markers were predictive of response to neoadjuvant chemotherapy before surgery which may be applicable as a clinical test to guide therapy ( Sigin et al, 2020 ). Second, CDH8 promoter hypermethylation has been documented in four head and neck cancer studies ( Ekanayake Weeramange et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that DNA methylation profiling may serve as novel tool in oncology for improved classification and differential diagnosis of carcinomas, especially brain tumors and sarcomas [26,27]. Moreover, the potential of DNA methylation pattern as prognostic or predictive marker of response to specific therapies including chemotherapy, targeted therapy and immunotherapy in several tumor types was reported previously [28][29][30].…”
Section: What Is Epigenetics?mentioning
confidence: 95%